Analisis Minat Siswa Terhadap Pembelajaran Kimia Hijau Berorientasi Chemo-Entrepreneurship - Lily Yunis; Suyatno Sutoyo; Isnawati; M Satriawan (Postgraduate, University of Mataram, 2025)
This study aims to determine how much student interest in learning chemistry through the Chemo-Entrepreneurship (CEP) approach integrated with the PjBL model. The integration of the PjBL model in CEP is done by learning chemistry that produces products that have economic value. The subjects of this study were students of SMA Negeri 19 Surabaya class X-5 in the academic year 2024-2025 The data collection technique in this study was purposive sampling with questionnaires and interviews The data obtained were then analysed with a Likert scale and descriptive analysis. The results showed that students' interest in Chemo-entrepreneurship oriented green chemistry learning was very high with a percentage of 85% expecting learning methods with experiments to produce useful and economically valuable products. In addition, student readiness is also very high with a percentage of 88% in participating in project-based green chemistry and Chemo-Entrepreneurship oriented learning.